2020
DOI: 10.12928/telkomnika.v18i2.14747
|View full text |Cite
|
Sign up to set email alerts
|

A robust method for VR-based hand gesture recognition using density-based CNN

Abstract: Many VR-based medical purposes applications have been developed to help patients with mobility decrease caused by accidents, diseases, or other injuries to do physical treatment efficiently. VR-based applications were considered more effective helper for individual physical treatment because of their low-cost equipment and flexibility in time and space, less assistance of a physical therapist. A challenge in developing a VR-based physical treatment was understanding the body part movement accurately and quickl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Gesture recognition, a fundamental aspect of hand tracking, allows users to communicate with virtual environments through a variety of hand gestures. In the study by Liliana et al [ 42 ], a pipeline combining movement sensors, a binary image representation of a gesture shape, and a density-based CNN was proposed. This pipeline, combined with HTC Vive, Kinect, and Leap Motion, has achieved accurate hand gesture recognition with a remarkable 97.7% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Gesture recognition, a fundamental aspect of hand tracking, allows users to communicate with virtual environments through a variety of hand gestures. In the study by Liliana et al [ 42 ], a pipeline combining movement sensors, a binary image representation of a gesture shape, and a density-based CNN was proposed. This pipeline, combined with HTC Vive, Kinect, and Leap Motion, has achieved accurate hand gesture recognition with a remarkable 97.7% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Another example of the application of visualisation may be seen in the interpretation of sign language through the use of hand movements [30]. In a similar vein, Chae et al [31] proposed a VR based hand gesture identification system that used a density based CNN. The visualisation connected with trajectory reconstruction has been demonstrated in Amar et al [32], and lastly, nature grasping has been revealed in Tian et al [33].…”
Section: Conceptualizationmentioning
confidence: 99%
“…This study depends on the weights of the transfer method that learns from shared weights among the source and target of pre-trained models. Therefore, it can be used to deliver more improvements in classification accuracy as well as reduce the total training interval [30]- [32].…”
Section: Deep Transfer Approachmentioning
confidence: 99%